Hematological profile in visceral leishmaniasis - Agrawal, Y; Sinha, AK; Upadhyaya, P; Kafle, SU; Rijal, S; Khanal, B (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Visceral Leishmaniasis is the most severe form of leishmaniasis and can be fatal in the absence of treatment. Nepal, India, Bangladesh, Brazil and Sudan constitute five countries of the world where more than 90% of visceral leishmaniasis occurs. The aim of this study is to evaluate haematological profile with available clinical data in visceral leishmaniasis patients and to detect LD bodies among them. MATERIALS AND METHODS: It is a hospital based cross sectional study conducted in the Department of Pathology, BPKIHS, Dharan, for the period of one year. LD bodies were calculated in bone marrow aspirate of forty clinically suspected cases by counting the number of parasites per 100 consecutive oil immersion fields. RESULTS: The age ranged from 2-60 years. Pyerxia was the most common sign (100%) followed by splenomegaly (82.5%), hepatomegaly (65%), and pallor (75%). Anemia was present in 90%, leucopenia in 67.5% and thrombocytopenia in 72.5% cases. Bicytopenia and pancytopenia were observed in 40% and 25% cases, respectively. On peripheral examination RBCs were predominantly normocytic normochromic. On bone marrow examination normocellular marrow and megaloblastic features were predominant findings followed by increased plasma cells. Low, moderate and high grade LD bodies were present in 7.5%, 37.5% and 55% of the cases respectively. Hepatomegaly, anemia, neutropenia and lymphocytosis were statistically significant to parasite load (p-value <0.05). CONCLUSIONS: Besides LD bodies in bone marrow aspirates, dyserythroblastic changes and increase plasma cells are common findings in leishmaniasis. Patient from endemic area with positive clinical history and findings should be examined for LD bodies in marrow if dyserythroblastic and increase plasma cell picture is found. DOI: http://dx.doi.org/10.3126/ijim.v2i2.8320 Int J Infect Microbiol 2013;2(2):39-44